Floristic Study of West Sumbawa, Indonesia - Harry Wiriadinata; Deden Girmansyah; James Hunter; W. Scoot Hoover; Kuswata Kartawinata (Research Center for Biology, 2013)
A floristic survey was undertaken in mountains forest of West Sumbawa and some surrounding lower forests, an area of Indonesia receiving limited biological study. Three hundred sixteen species of Angiosperms and ferns were collected from this area in 2004 and 2005. The collection represents 101 families and 234 genera.